(untitled) (International journal of artificial intelligence, 2025)
The preservation of animal embryos is a crucial practice in reproductive biotechnology, genetic conservation, and scientific research. Various methods have been developed for storing embryos to ensure their viability for future use, including cryopreservation, embryo culture, and the use of stem cells. Cryopreservation, especially in its vitrification form, is the most widely utilized technique, allowing embryos to be frozen and stored indefinitely in liquid nitrogen. This method has been successfully applied to a range of species, including cattle, horses, and laboratory animals. In addition to cryopreservation, oocyte freezing, embryo splitting, and emerging technologies like artificial scaffolding and somatic cell nuclear transfer offer alternative ways to preserve genetic material and enhance breeding programs. The preservation of animal embryos is integral to maintaining genetic diversity, facilitating research, and supporting the livestock and wildlife industries. This abstract provides an overview of current techniques for animal embryo preservation and their applications.